Plasma tissue factor coagulation activity in post-acute myocardial infarction patients - Lim, Xiong Chang; Yatim, Siti Maryam J. M.; Chong, Suet Yen; Wang, Xiaoyuan; Tan, Sock Hwee; Yang, Xiaoxun; Chan, Siew Pang; Richards, A Mark; Charles, Chris J.; Chan, Mark Y.; Wang, Jiong-Wei (Frontiers in Endocrinology, 2022)
Introduction Coagulation is involved in fibroproliferative responses following acute myocardial infarction (AMI). Left ventricular (LV) remodeling following AMI is closely associated with progression to heart failure. This study aims to assess the association between plasma tissue factor activity and LV remodeling in post-AMI patients. Methods We studied 228 patients with AMI and 57 healthy subjects. Patients with AMI were categorized into two age- and sex-matched groups: patients with adverse LV remodeling or reverse LV remodeling, defined by an increase or decrease, respectively, in LV end systolic volume by ≥15% over 6 months. TF activity was measured in plasma collected at baseline (within 72 hours of revascularization), 1 month and 6 months post-AMI. Multiple level longitudinal data analysis with structural equation (ML-SEM) model was used to assess the impact of various clinical variables on TF activity in post-AMI. Results Plasma TF activity in post-AMI patients at baseline (29.05 ± 10.75 pM) was similar to that in healthy subjects but fell at 1 month (21.78 ± 8.23, p<0.001) with partial recovery by 6 months (25.84 ± 8.80, p<0.001) after AMI. Plasma TF activity at 6 month post-AMI was better restored in patients with reverse LV remodeling than those with adverse LV remodeling (27.35 ± 7.14 vs 24.34 ± 9.99; p=0.009) independent of gender, age and relevant cardiovascular risk factors. Conclusions Plasma TF activity decreased after AMI but was better restored at 6 months in patients with reverse LV remodeling. The clinical significance of changes in post-AMI plasma TF activity needs further investigation.